2020
DOI: 10.1002/essoar.10502512.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-point Conjugate Observations of Dayside ULF Waves during an Extended Period of Radial IMF

Abstract: Long-lasting Pc5 ultralow frequency (ULF) waves spanning the dayside and extending from L ∼ 5.5 into the polar cap region were observed by conjugate ground magnetometers. Observations from MMS satellites in the magnetosphere and magnetometers on the ground confirmed that the ULF waves on closed field lines were due to fundamental toroidal standing Alfvén waves. Monochromatic waves at lower latitudes tended to maximize their power away from noon in both the morning and afternoon sectors, while more broadband wa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…The region of largest δB 2 z has a width of approximately 14 d i (∼ 1.2R E ). In addition to the dipole tilt, which places the northern cusp further towards the dayside, the north-south asymmetry in fluctuations in both runs is also affected by the different locations of the quasi-parallel shock, consistent with observations of magnetic field perturbations under quasi-radial IMF conditions (Shi et al, 2020). The structure of magnetic field lines in both cases at selected times is shown in Fig.…”
Section: Overall Structure and Fluctuationssupporting
confidence: 86%
See 1 more Smart Citation
“…The region of largest δB 2 z has a width of approximately 14 d i (∼ 1.2R E ). In addition to the dipole tilt, which places the northern cusp further towards the dayside, the north-south asymmetry in fluctuations in both runs is also affected by the different locations of the quasi-parallel shock, consistent with observations of magnetic field perturbations under quasi-radial IMF conditions (Shi et al, 2020). The structure of magnetic field lines in both cases at selected times is shown in Fig.…”
Section: Overall Structure and Fluctuationssupporting
confidence: 86%
“…Wang et al, 2009;Omidi & Sibeck, 2007;Palmroth et al, 2013) under different IMF conditions. Under IMF with a strong radial component, the cusp has been observed to be highly dynamic (Taylor et al, 2004), and it has been shown that the turbulence in the ion foreshock can lead to ULF waves on the open and closed field lines of the polar cap (Shi et al, 2020). Other statistical observa-tions have shown the structure of the cusp and its boundaries under various IMF conditions (Lavraud et al, 2004(Lavraud et al, , 2005Pitout et al, 2012), and statistical studies of cusp structure and motion are shown in (Pitout et al, 2006(Pitout et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%